2000
DOI: 10.1007/pl00013789
|View full text |Cite
|
Sign up to set email alerts
|

Effect of anabolic/androgenic steroids on myosin heavy chain expression in hindlimb muscles of male rats

Abstract: We have examined the effect of male sex hormones on the myosin heavy chain (MHC) expression of the soleus and extensor digitorum longus (EDL) muscles. Young male adult Wistar rats were treated over a 25-day period with either oil (CON, n = 8), nandrolone (nortestosterone decanoate, NAN, n = 8), nandrolone combined with endurance exercise (treadmill running, NAN+EXE, n = 8), or were castrated (CAS, n = 8). The MHC composition of the soleus and EDL muscles was measured by electrophoresis. Castration and treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 17 publications
1
10
0
Order By: Relevance
“…Because we preferred to use the single fibers for nitrotyrosine detection, it was not possible to determine myosin heavy chain (MHC) isoform composition of the single fibers. However, MHC isoform composition of rat soleus muscle consists almost exclusively of the slow isoform (12,(33)(34)(35). Therefore, it is very unlikely that nonuniform distribution of MHC isoform composition between fibers of different experimental groups has influenced the robust changes in single fiber contractility between groups, as observed in the present study.…”
Section: Nitrotyrosine Measurementmentioning
confidence: 58%
“…Because we preferred to use the single fibers for nitrotyrosine detection, it was not possible to determine myosin heavy chain (MHC) isoform composition of the single fibers. However, MHC isoform composition of rat soleus muscle consists almost exclusively of the slow isoform (12,(33)(34)(35). Therefore, it is very unlikely that nonuniform distribution of MHC isoform composition between fibers of different experimental groups has influenced the robust changes in single fiber contractility between groups, as observed in the present study.…”
Section: Nitrotyrosine Measurementmentioning
confidence: 58%
“…Previous investigations have shown a direct effect of AAS treatment on muscle mass, contractile properties, and on the expression of myosin heavy-chain isoforms [13,16,17]. The results have demonstrated that a short period (6 weeks) of nandrolone decanoate treatment in the absence of exercise increases twitch tension and the sensitivity of the ryanodine receptor to caffeine at low concentrations tested, suggesting some modifications in the excitation-contraction coupling mechanism [16].…”
Section: Introductionmentioning
confidence: 74%
“…1997), myosin (Tsika et al . 1987) and MHC isoforms (Noirez & Ferry 2000) in fast‐twitch muscle. Further experiments are necessary to assess whether nandrolone decanoate treatment induces changes in the expression of troponin C isoforms.…”
Section: Discussionmentioning
confidence: 99%